Halo-halo the mixture of language in Philippine media - Ladringan, Czarina B.
The study, The Mixture of Language in Philippine Media, deals with how broadcast media affects the verbal interaction and attitudes of Filipinos. It aims to found out whether the language used in television, news programs in particular, influence the language preference and use of students in the formal and informal classroom settings. The perceptions of the audience regarding the language used in newscasts, specifically Pulso, TV Patrol, Frontpage and Saksi, and the definition of people in media and students of the language employed in the said shows is likewise identified by the study. One hundred respondents from different colleges in the University of the Philippines in Diliman were surveyed to determine the perceptions of the students on the language used in the newscasts as well as their definition of the language. It likewise discerned the students' views on the appropriateness of the identified language when used in the formal or informal classroom settings. In order to ascertain the views of the media sector, two key informant interviews were conducted, Karen Padilla from ABS-CBN and Raffy Marcelo from GMA 7. The verbal interaction patterns of the students were observed through the three focus group discussions carried out by the researchers. The study showed that students accept the use of Taglish in news programs but prefer to use English in the formal classroom setting. It was also gathered from the findings of the study that news programs are not effective channels in initiating a change in the language preference and use of the students.